IDENTIFIKASI KINETIKA PERTUMBUHAN ALGA PADA MODEL MONOD - Mochamad Bagus Hermanto; A.J.B. Boxtel; K.J. Keesman (Faculty of Agricultural Technology, University of Jember, 2011)
Algae are one of potential source for renewable energy. Algae growth depends on many inputs (i.e. light, temperature, and nutrition). Mathematical model can be developed to study the development of algae during cultivation. This research deals with the design of experimental method to study the kinetic of algae growth. Optimal input design was introduced to Monod models. Light intensity and dilution used as input. Two parameters i.e: maximum specifics-rate-growth (μmax) and saturation-constant at light intensity (KI) were estimated. Correlation coefficient between (μmax) and (KI) parameters was observed. The results showed that the Monod models perform better than conventional models. This design can minimize confidential interval. Keywords: algae growth, parameter estimation, optimal input design